Territori di carta (2020)
Cartography represents places through symbols related to forms, dimensions and signs. By the meticulous decoding of all these signs and their connexions the user is enabled to enter the deep identity of places considered. The book is based on a rational consequential method by which the user can get the necessary information from the map in order to understand and imagine the represented places, so as to use it for personal aims. The book is primarily intended for specialists or students of territory, but also for hikers who use maps on excursions or just for people who are curious and interested in deepening their knowledge of territory.